On the Mean Values of the Dirichlet Series - Zelisko, M. M.; Sheremeta, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
For Dirichlet series with arbitrary abscissa of absolute convergence, we investigate the relationhip between the increase in the maximum term and \(( olimits_n = 1^∞ | a_n |^q { qσ λ _n } )^1/q\) , q ∈ (0,+∞).